Reading Questions in "English for Nusantara" Textbook by Using Revised Bloom's Taxonomy - Anggrianto Arlansyah; Hilda Puspita; Eko Saputra (Journal of English Education and Teaching, 2023)
This study aims to determine the categories of cognitive process dimension contained in the textbook “English for Nusantara” and to find the proportion of cognitive process dimensions between LOTS and HOTS in the textbook “English for Nusantara” using the Revised Bloom Taxonomy. This research was a descriptive quantitative research. The subject of this research was the textbook "English for Nusantara" for grade 7 junior high school in the 2022/2023 academic years. This study used a checklist instrument to collecting data. The results of this study: 1) There are 3 categories of cognitive process dimensions in the reading questions in the textbook "English for Nusantara" namely remembering, understanding and analyzing. 2) The proportion between LOTS and HOTS was 92.10% of the reading questions in the textbook “English for Nusantara” are LOTS and 7.89% of the questions are HOTS. It means LOTS was more dominant than HOTS in reading questions in the textbook "English for Nusantara". This research found that reading questions in “English for Nusantara” textbook not appropriate with the achievements of junior high school English learning in the Merdeka curriculum. As a suggestion, reading questions in the textbook "English for Nusantara" should be appropriate with learning outcomes. Thus, there needs to be an evaluation to appropriate with the achievements of junior high school English learning in the Merdeka curriculum. Teachers can also modify learning or use other supporting textbooks. Thus, learning will be appropriate with the achievements of junior high school English learning in the Merdeka curriculum.